Fluoxetine treatment prevents the inflammatory response in a mouse model of posttraumatic stress disorder. (May 2016) - Kao, Chi-Ya; He, Zhisong; Zannas, Anthony S.; Hahn, Oliver; Kühne, Claudia; Reichel, Judith M.; Binder, Elisabeth B.; Wotjak, Carsten T.; Khaitovich, Philipp; Turck, Christoph W.
Abstract: Despite intense research efforts the molecular mechanisms affecting stress-vulnerable brain regions in posttraumatic stress disorder (PTSD) remain elusive. In the current study we have applied global transcriptomic profiling to a PTSD mouse model induced by foot shock fear conditioning. We compared the transcriptomes of prelimbic cortex, anterior cingulate cortex (ACC), basolateral amygdala, central nucleus of amygdala, nucleus accumbens (NAc) and CA1 of the dorsal hippocampus between shocked and non-shocked (control) mice, with and without fluoxetine treatment by RNA sequencing. Differentially expressed (DE) genes were identified and clustered for in silico pathway analysis. Findings in relevant brain regions were further validated with immunohistochemistry. DE genes belonging to 11 clusters were identified including increased inflammatory response in ACC in shocked mice. In line with this finding, we noted higher microglial activation in ACC of shocked mice. Chronic fluoxetine treatment initiated in the aftermath of the trauma prevented inflammatory gene expression alterations in ACC and ameliorated PTSD-like symptoms, implying an important role of the immune response in PTSD pathobiology. Our results provide novel insights into molecular mechanisms affected in PTSD and suggest therapeutic applications with anti-inflammatory agents.